ANALISIS USAHATANI PADI ( Oryza sativa L. var. ciherang ) DI KELOMPOK TANI “TANI MAKMUR II” DESA GERDU KECAMATAN PECANGAAN KABUPATEN JEPARA - Neti Herawati; Harum Sitepu; Rumiyadi Rumiyadi (Fakultas Pertanian, Universitas Janabadra, 2023)
This research was conducted in Gerdu village Pecangaan district Jepara regency in January - March 2023. The purpose of this study was to determine income analysis, financial feasibility and the effect of production facility costs (seeds, fertilizers, pesticides) and labor on the income of the ciherang variety rice farming business. The method used in this research is to do descriptive analysis and ex post facto. The method of determining the sample is the census method with data collection, namely primary data and secondary data. Methods of data analysis using calculations: production costs, revenues, total costs. To calculate the financial feasibility of farming using the parameters RCR, ROI, price BEP, production BEP, while to determine the cost of production facilities (seeds, fertilizers, pesticides) and labor on income used multiple linear regression analysis. The research results show: 1). The average income of ciherang variety rice farming is IDR 19,760,327.-/ hectare per one growing season, with an RCR feasibility of 2.67 (≥ 1), BEP(Q) = 2.508 Kg ( real 6.625 Kg ), BEP(IDR)= Rp. 1,836.- (real Rp. 4800, -), and ROI = 166.53% , 2). Analysis of the cost of production facilities (seeds, fertilizers, pesticides and labor) obtained the equation Y = - 2145670.297+35.762 X1 ** -13,550 X2 ** +2,152 X3ns +4,677 X4 **. Conclusion: Farming analysis of ciherang variety rice in the farmer group